2007
DOI: 10.1016/j.vaccine.2006.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular rather than oral administration of replication-defective adenoviral vaccine vector induces specific CD8+ T cell responses in the gut

Abstract: Gut-associated lymphoid tissue (GALT) is the primary replication site for HIV-1, resulting in a pronounced CD4 + T cell loss in this tissue during primary infection. A mucosal vaccine that generates HIV-specific CD8 + T cells in the gut could prevent the establishment of founder populations and broadcasting of virus. Here, we immunized mice orally and systemically with a chimpanzee derived adenoviral vector expressing HIV gag (AdC68gag) and measured frequencies of gag-specific interferon-gamma (IFN-γ) producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
(51 reference statements)
1
38
1
Order By: Relevance
“…administration is capable of inducing mucosal immune responses, as a high-dose i.m. administration might be distributed to peripheral mucosal sites or lymphoid organs draining such sites (21). Conversely, our reports of highly persistent immunological surveillance in the f.p.-injected target organ may help explain why intranasal virus administration may induce persistent T cell responses at this site only (63).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…administration is capable of inducing mucosal immune responses, as a high-dose i.m. administration might be distributed to peripheral mucosal sites or lymphoid organs draining such sites (21). Conversely, our reports of highly persistent immunological surveillance in the f.p.-injected target organ may help explain why intranasal virus administration may induce persistent T cell responses at this site only (63).…”
Section: Discussionmentioning
confidence: 70%
“…infection can mediate cytotoxicity ex vivo and in vivo and protect against a vaccinia virus challenge i.p. ; thus, even though these cells cannot easily be mobilized to a site of infection, it remains a possibility that mucosal immune responses induced by highdose vaccination will prove effective against a localized mucosal challenge (this has not yet been addressed in published studies) (21). However, it must be stressed that previous studies using adenoviral vectors in humans have found a dose ceiling of ∼10 11 particles (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the requirement for mucosal immunization to generate protective "frontline immunity" against mucosal pathogens is highly controversial. On the one hand, numerous studies in the literature have demonstrated that immune responses are readily detectable at mucosal sites following systemic delivery of vaccines, and complete or partial protection from mucosal challenge is attainable (2,(33)(34)(35)(36)(37)(38)(39)(40). Systemic immunization is adequate for successful vaccines for some mucosal pathogens, notably the polio virus and the influenza virus, where high titers of neutralizing Abs are capable of clearing cellfree virus and preventing disease (34,41).…”
mentioning
confidence: 99%
“…Also, regarding the ability to apply vaccines in manners that will induce local immunosurveillance at the likely site of virus entry or early replication, adenoviral vaccines have been found to be very useful. Thus, studies have suggested that local application can be used to augment mucosal CD8+ T cell memory (Belyakov et al, 2008;de Souza et al, 2007;Kaufman et al, 2010;Lemiale et al, 2007), and also that parenteral immunization can be used to induce T cell homing to mucosal sites (Haut et al, 2010;Kaufman et al, 2010;Lin et al, 2007;Tatsis et al, 2007b). The ability to induce local T cell responses is not a quality unique to adenovirus vectors and local immunity can also be obtained by mucosal application of pox-viral vectors (Corbett et al, 2008).…”
Section: Disease Indications Where the Attributes Of Adenoviral Vectomentioning
confidence: 99%